Correction: Hematological Adaptations to Training With and Without Heat - Sebastien Racinais; David Nichols; Nathan Townsend; Gavin Travers; Scott Cocking; Harry A. Brown; Jonathan Rubio; Julien D. Périard (Journal of Science in Sport and Exercise, 2025)

Hematological Adaptations to Training With and Without Heat - Sebastien Racinais; David Nichols; Nathan Townsend; Gavin Travers; Scott Cocking; Harry A. Brown; Jonathan Rubio; Julien D. Périard (Journal of Science in Sport and Exercise, 2024)

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Skeletal muscle oxidative adaptations following localized heat therapy - Mohammed Ihsan; Mariem Labidi; Sebastien Racinais (European Journal of Applied Physiology, 2023)
Repeated heat treatment has been shown to induce oxidative adaptations in cell cultures and rodents, but similar work within human models is scarce. This study investigated the effects of 6 weeks of localized heat therapy on near-infrared spectroscopy-(NIRS) derived indices of muscle oxidative and microvascular function. Twelve physically active participants (8 males and 4 females, age: 34.9 ± 5.9 years, stature: 175 ± 7 cm, body mass: 76.7 ± 13.3 kg) undertook a 6-week intervention, where adhesive heat pads were applied for 8 h/day, 5 days/week, on one calf of each participant, while the contralateral leg acted as control. Prior to and following the intervention, the microvascular function was assessed using NIRS-based methods, where 5 min of popliteal artery occlusion was applied, and the reperfusion (i.e., re-saturation rate, re-saturation amplitude, and hyperemic response) was monitored for 2 min upon release. Participants also performed a 1-min isometric contraction of the plantar flexors (30% maximal voluntary contraction), following which a further 2 min interval was undertaken for the assessment of recovery kinetics. A 20-min time interval was allowed before the assessment protocol was repeated on the contralateral leg. Repeated localized heating of the gastrocnemius did not influence any of the NIRS-derive indices of microvascular or oxidative function ( p > 0.05) following 6 weeks of treatment. Our findings indicate that localized heating via the use of adhesive heat pads may not be a potent stimulus for muscle adaptations in physically active humans.

Heat adaptation in humans with controlled heart rate heat acclimation - Julien D. Périard; Sebastien Racinais; Michael N. Sawka (European Journal of Applied Physiology, 2021)

Muscle variables of importance for physiological performance in competitive football - Magni Mohr; Martin Thomassen; Olivier Girard; Sebastien Racinais; Lars Nybo (European Journal of Applied Physiology, 2016)